THE ROLE OF AVIOBRIDGE FOR SERVICES FLIGHTS - Khoiriyah, Hidayatul; Utomo, Wasito; Fatmawati, Fatmawati (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Aviobridge usage services are one of the revenues in airport management. In this case by PT. Angkasa Pura II. One of the airport's revenues is the service of using aviobridge facilities. In providing flight services, Sultan Thaha Jambi Airport is supported by 2 (two) units of aviobridge facility equipment, but the current condition of the aviobridge facilities cannot operate optimally. Therefore, to find out the role of aerobridges for flight services at Sultan Thaha Jambi airport, by conducting a study or simple research (qualitative descriptive) with data collection methods using observation and interviews, and analyze data to obtain alternative problem solving. The result of this study is that the maintenance of aerobridges at Sultan Thaha Jambi Airport must be improved and the operation of bridges carried out in accordance with procedures set by the airport. Because the maintenance and operation of aviobridge facilities have an influence on improving the performance of aviobridge and improving the quality of service to passengers and airlines as users of aviobridge services at Sultan Thaha Jambi Airport.